Sistem Informasi Keuangan Pada Koperasi Peneti Kelurahan Maahas Kabupaten Banggai - Trisno Wibowo Kandakon; Khadija Nurmin A. Ido (Akademi Manajemen Informatika dan Komputer Luwuk Banggai, 2022)
This research aims to design and build a web-based financial information system for research cooperatives so that they can help and facilitate the cooperative when collecting data on members and on cooperative financial reports. The research methods used in this research are description methods and data collection methods used in this research, namely observation, interview and literature study methods. The observation method is a method of collecting data by means of research which is carried out directly at the research location, the method of interviewing informants to obtain accurate information, and the method of literature study, namely the method of collecting data raised in the title for the preparation of this final project. The results obtained in this research are that a financial information system can be built for the research cooperative using the PHP programming language, HTML and MySQL database, which produces a financial information system for the research cooperative in the Maahas village. The conclusion from the construction of a financial information system for the research cooperative is expected to facilitate the management of the Peneti cooperative in collecting data on members, member savings, loans and refunds as well as financial reports and can process a more effective reporting process that can be used easily by users of the Financial Information System in the Web-Based Peneti Cooperative